Serial mediating role of transformational leadership and perception of artificial intelligence use in the effect of employee happiness on innovative work behaviour in nurses - Ferhat Onur Agaoglu; Murat Bas; Sinan Tarsuslu; Lokman Onur Ekinci (BMC Nursing)
Abstract Background Increasing quality and efficiency in health services can directly relate to nurses’ innovative work behaviors. The happiness levels of nurses at the workplace can positively affect their innovative work behaviors and their willingness to make a positive difference in patient care. In this context, the study aims to examine the serial mediation role of these factors by associating the effect of nurse happiness on innovative work behaviors with transformational leadership and perception of artificial intelligence use. Methods Nurses working in two medium-sized public hospitals in the Eastern Black Sea region of Turkey were selected as the study sample. Data were collected from 458 nurses by convenience sampling method. In this cross-sectional study, scales whose validity and reliability were supported by other studies were used. Results When the findings of the study were evaluated, a significant positive relationship was found between nurses’ happiness and innovative work behavior. In addition, it was found that transformational leadership and perception of AI usage had a mediating role separately in the relationship between nurses’ happiness and innovative work behavior. Finally, when the research model was tested, it was also determined that transformational leadership and perception of AI use have a serial mediating role in the relationship between nurses’ happiness and innovative work behavior. Conclusions This study revealed that nurse happiness has a significant and positive effect on innovative work behaviors, and transformational leadership and perception of artificial intelligence use have a serial mediating role in this relationship. Ultimately, this research offers some theoretical and practical implications for practitioners by emphasizing the strategic importance of transformational leadership practices and the integration of artificial intelligence technologies, as well as increasing the happiness levels of nurses to promote innovation in healthcare services.